2014
DOI: 10.1021/jp506874q
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Reversible First-Order Single Crystal to Single Crystal Phase Transition in Boc-γ4(R)Val-Val-OH: Interplay of Enthalpy and Entropy

Abstract: Crystals of Boc-γ(4)(R)Val-Val-OH undergo a reversible first-order single crystal to single crystal phase transition at Tc ≈ 205 K from the orthorhombic space group P22121 (Z' = 1) to the monoclinic space group P21 (Z' = 2) with a hysteresis of ∼2.1 K. The low-temperature monoclinic form is best described as a nonmerohedral twin with ∼50% contributions from its two components. The thermal behavior of the dipeptide crystals was characterized by differential scanning calorimetry experiments. Visual changes in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The enthalpy at the exothermic and endothermic peaks was −0.69 and 0.67 kJ·mol −1 , respectively. This small thermal hysteresis might be a general feature of SCSC transition because small hysteresis was reported also in the previous papers [4,7,10]. DSC curves in wide temperature ranges indicated no existence of additional phase transition ( Figure S1).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The enthalpy at the exothermic and endothermic peaks was −0.69 and 0.67 kJ·mol −1 , respectively. This small thermal hysteresis might be a general feature of SCSC transition because small hysteresis was reported also in the previous papers [4,7,10]. DSC curves in wide temperature ranges indicated no existence of additional phase transition ( Figure S1).…”
Section: Resultssupporting
confidence: 83%
“…Hence, the reversible SCSC phase transition is a fascinating phenomenon because of its potential applications in ferroelectric and switchable dielectric devices [1][2][3]. Several molecular crystals that undergo temperature-induced reversible SCSC phase transition have been reported [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these antecedents we decided to investigate the closely related species 4 0 -(isoquinolin-4-yl)-4,2 0 :6 0 ,4 00 -terpyridine (iqtp), which possesses a similar coordination capacity to ptp and where the only difference is the metal-binding fused-ring isoquinolin-4-yl instead of 4 0 -pyridyl. Unexpectedly, during the structural study by X-ray diffraction we observed a temperature-dependent single-crystal to single-crystal first-order phase transition, a phenomenon that, although not new in organic crystals (Pal et al, 2014;Drebushchak et al, 2011;Kubicki, 2004), to the best of our knowledge is novel in this type of terpyridine-based compound.…”
Section: Introductionmentioning
confidence: 76%
“…Conformational flexibility in the crystalline state may contribute to an order-disorder phase transition in which different conformers co-exist in the high-temperature form and are transformed into a single stable conformer in the low-temperature form upon cooling; this transformation may or may not be associated with a change in the space group (Quah et al, 2012). Temperatureinduced translationengleiche group-subgroup relations such as the monoclinic-to-orthorhombic phase transition observed in barbituric acid dihydrate (P2 1 /n $ Pnma) (Nichol & Clegg, 2005) and Boc-4 (R)Val-Val-OH crystals (P2 1 $ P22 1 2 1 ) (Pal et al, 2014) result in twinned crystals, whereas klassengleichetype phase transitions associated with loss of translational symmetry will produce antiphase domains (Mü ller, 2013). In these cases, as well as in the title compound, the lowtemperature and low-symmetry phases are monoclinic pseudomerohedral or nonmerohedral twins.…”
Section: Introductionmentioning
confidence: 99%